2012
DOI: 10.1080/02786826.2011.617795
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Reactive Oxygen Species (ROS) in Mainstream and Sidestream Cigarette Smoke

Abstract: Reactive oxygen species (ROS) have been related to adverse health effects in recent years. Previous studies have reported ROS concentrations in mainstream smoke, but the reports have shown considerable variability and conclusions. There have been no prior measurements on sidestream smoke. In this study, the amounts of gas-phase and particle-bound ROS in tobacco smoke were determined using 2 ,7 -dichlorodihydrofluorescin diacetate (DCFH-DA) as the fluorescent probe with hydrogen peroxide as the standard. Both r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 28 publications
1
46
1
Order By: Relevance
“…However, the ROS content found in our study was significantly lower than in studies on combustion samples (Kao and Wang 2002;Zhao and Hopke 2011). This suggests that our aged brake wear samples may act similarly to most ambient air pollution particles upon deposition in the lungs and lead to ROS-formation.…”
Section: Acellular Ros Generationcontrasting
confidence: 55%
See 1 more Smart Citation
“…However, the ROS content found in our study was significantly lower than in studies on combustion samples (Kao and Wang 2002;Zhao and Hopke 2011). This suggests that our aged brake wear samples may act similarly to most ambient air pollution particles upon deposition in the lungs and lead to ROS-formation.…”
Section: Acellular Ros Generationcontrasting
confidence: 55%
“…It has been verified (Wardman 2007;Venkatachari and Hopke 2008;Sauvain et al 2012) and widely applied (Hung and Wang 2001;Venkatachari et al 2005;Zhao and Hopke 2011). An additional advantage of DCFH for this study was that it allowed the use of the same reactant in both the cell-free and the cell-culture-based measurements.…”
Section: Acellular Ros Generationmentioning
confidence: 99%
“…ROS exist both in the gas phase and in PM. ROS are either produced inside the human body through generation by the inhaled PM (e.g., by transition metals) in vivo (endogenous ROS) or by transportation into the lungs on respirable particles (exogenous ROS) (Zhao and Hopke, 2012). While gas-phase ROS are most likely removed in the upper mucus membranes through diffusion (Kao and Wang, 2002), ROS associated with fine particles can penetrate deeply into the lungs, causing oxidative stress and cell damage.…”
Section: Introductionmentioning
confidence: 99%
“…However, activated carbon had higher ROS scavenging power, similar to TBHQ, in our experiments. This maybe because that smoke ROS existed mainly in the particles of cigarette smoke and could be substantially absorbed by activated carbon due to its high degree of microporosity (Zhao and Hopke 2012;Branton and Bradley 2011). Therefore, it could be concluded that the effect of filter additives on the reduction of ROS in cigarette smoke could be based on their antioxidant activity and=or adsorption capacity toward particles that contain large amount ROS in cigarette smoke.…”
Section: Fluorescence Evaluation Ros Scavenging Efficiency 687mentioning
confidence: 97%
“…More recently, several fluorescence probes, such as 2, 7-dichlorofluorescein (DCFH), dihydrorhodamine 123, and dihydrorhodamine 6 G (DHR 6 G) have been applied for the detection of ROS in cigarette smoke (Huang, Lin, and Ma 2005;Ou and Huang 2006;Zhao and Hopke 2012). These compounds are nonfluorescent but when oxidized by typical ROS (e.g., O ÀÁ 2 , HO·, R·, RO·, and ROO·), or H 2 O 2 in the presence of horseradish peroxidase they become highly fluorescent dyes that can be quantitatively determined by a fluorescence spectrophotometer.…”
Section: Introductionmentioning
confidence: 99%